(untitled) (Signifikan: Jurnal Ilmu Ekonomi, 2021)
This research was conducted to discover the relationship between Islamic crowd investing and agriculture by exploring and analyzing the Islamic crowd-investing platform, and to describe the importance and benefits of sustainable agriculture in Indonesia. Funding platforms for agriculture are still relatively small in Indonesia. However, the potential for this sector is still very high due to the large number of demands and a large market. A systematic literature review with a qualitative approach research method was used in this study, specifically to review the literature retrieved from computerized databases, manual search, and authoritative texts related to Islamic crowd-investing and sustainable agriculture. This study showed a strong relationship explaining that financial technology, such as Islamic crowd-investing, has an important role not only in terms of funding, but also in achieving sustainable agriculture, which will have an impact on the environment that may potentiate the agricultural sector itself. JEL Classification: O13, Q14 How to Cite: Purnamasari, I., & Kassim, S. (2021). The Role of Islamic Crowd-Investing for Sustainable Agriculture in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 10(2), 343-358. https://doi.org/10.15408/sjie.v10i2.20060.